Process and Skills Involved in Website Translation and Its Relevance to Translation Teaching - Ahmad Taufiq (Kayon Media, 2018)
This research is based on the phenomenon of application communicative learning method that frequently used by instructors in English courses. In general this method is assumed can fulfill the learners need, because it’s really helpful the learners to learn and command of English. Based on the research focus, so the whole research problems accomplished by qualitative approach that is case study to reveal the phenomenon that happened deeply in NSC English course institution of Pandaan. From the analyses data, application of communicative method in learning English is conducted interactively, those are asking and respond, discussion, presentation, dialogue, and simulation; role-play and also conducted by monologue (story telling).Penelitian ini didasarkan atas fenomena penggunaan metode pembelajaran komunikatif, yang kerap kali dipakai oleh para instruktur dalam kursus bahasa Inggris. Pada umumnya metode ini dianggap dapat memenuhi kebutuhan warga belajar, karena sangat membantu warga belajar dalam mempelajari dan menguasai bahasa Inggris. Berdasarkan fokus penelitian maka secara keseluruhan masalah penelitian ini diselesaikan dengan pendekatan kualitatif berupa studi kasus untuk mengungkapkan fenomena-fenomena yang terjadi secara menyeluruh dan mendalam pada lembaga kursus Bahasa Inggris Dari analisis data, penerapan metode komunikatif pembelajaran bahasa dilakukan secara interaktif, yaitu dengan tanya jawab, diskusi, presentasi, percakapan, dialog, dan simulasi yaitu bermain peran, dan juga dilakukan secara monolog yaitu bercerita (story telling).